Sustainable hydrate inhibition: Pectin and MEG synergy for deep-sea environments - Ankur Singh; Shanker Krishna; Ajay Suri; Lavish Kumar Singh; Isaac Wilson (Natural Gas Industry B)
To ensure the continuous operation of the oil and gas industry, it is imperative to maintain an uninterrupted flow of oil and gas through pipelines and pay specific attention to preventing disruptions caused by hydrate blockages. Kinetic hydrate inhibitors (KHIs) have garnered considerable interest due to their capacity for effective hydrate prevention with minimal dosages typically ranging from 0.5 wt% to 2 wt%, guaranteeing both safety and efficiency. While some KHIs, such as amino acids and certain classes of ionic liquids, are known to be biodegradable, it is crucial to explore, develop, and thoroughly evaluate more natural and sustainable alternatives to these KHIs. This study investigated the potential of pectin as a biodegradable HI and examines its performance in synergism with monoethylene glycol (MEG). To assess its inhibitory performance, we conducted measurements of the induction time (IT) and hydrate nucleation temperature (T0) essential for hydrate formation under different conditions. The experimental outcomes indicated that pectin demonstrated slightly lower performance in comparison with commercial KHIs. However, its performance improved significantly when combined with a concentration of MEG. A blend of 0.25 wt% pectin and 2 wt% MEG offered an IT of 6.53 h, while poly(vinyl pyrrolidone) (PVP) and poly(vinyl caprolactam) (PVCap) at 0.25 wt% provided ITs of 4.9 h and 5.9 h, respectively. IT escalated from 2.13 h at 0 wt% MEG to 7.99 h at a MEG concentration of 5 wt%, while T0 exhibited a notable decrease from 8.32 °C at 0 wt% MEG to 1.39 °C at 5 wt% MEG. The identified synergy between pectin and MEG in hydrate inhibition suggests substantial potential for advancing deep-sea hydrate risk management strategies in future research.